The relationship between the Hippo signaling pathway and bone metastasis of breast cancer - Han, Qinyu; Qiu, Shi; Hu, Huiwen; Li, Wenjing; Dang, Xiangguo; Li, Xiangqi (Frontiers in Oncology, 2023)
Bone is the most common site of metastasis from breast cancer, which is the most prevalent cancer affecting women globally. Bone metastasis from breast cancer severely affects the quality of life of patients and increases mortality. The molecular mechanisms of metastasis, colonization, and proliferation of breast cancer cells in bone are complex and involve the interaction between breast cancer cells and the bone microenvironment. However, the precise mechanism is not clear at present. In recent years, the Hippo signaling pathway has attracted much attention due to its important role in regulating the expression of major effector molecules during tumor development. In particular, studies have found that the mutation and aberrant expression of the core components of the Hippo signaling pathway affect breast cancer cell migration and invasion, indicating that this pathway plays a role in bone metastasis, although the molecular mechanism of this pathway in breast cancer metastasis has not been fully elucidated. In this review, we discuss the function of the Hippo signaling pathway, introducing its role in breast cancer metastasis, especially bone metastasis of breast cancer, so as to lay a solid theoretical foundation for further research and for the development of effective targeted therapeutic agents.